Die vorderasiatischen Rollsiegel der Sammlungen “Bibel + Orient” der Universität Freiburg Schweiz = The ancient Near Eastern cylinder seals of the collections “Bible + Orient” of the University of Fribourg - Keel-Leu, Hildi. (Fribourg ; Göttingen)
xxi, 472 s.